A new species of Anurophorus (Collembola: Isotomidae) from South Korea, with notes on its molecular data - Chang, Gyu-Dong; Potapov, Mikhail; Park, Kyung-Hwa (Zootaxa, 2021)
A new species, Anurophorus hallaensis sp. nov. was collected from the withered leaves of Korean fir (Abies koreana Wilson), which is distributed at higher than 1,300 m in altitude on Mt. Hallasan (Jeju Island, South Korea). The morphology and two partial gene regions of this species are described herein. Anurophorus hallaensis sp. nov. showed the same formulas of macrochaetae and sensilla on thoracic segment II to abdominal segment IV as those exhibited by A. laricis Nicolet and A. palearcticus Potapov; however, this new species can be distinguished from them by the number of knobbed hairs on ventral side of legs. Partial DNA sequences of the mitochondrial Cytochrome c Oxidase subunit I (COI) gene and ribosomal DNA (28S rDNA) were used as DNA barcodes to distinguish between A. hallaensis sp. nov. and closely related congeners. The results of the present study indicate that the COI and rDNA are useful for species discrimination within the genus Anurophorus. An identification key to the Korean species of Anurophorus is provided.